Satellite evidence for pervasive water eutrophication in the Doce River reservoirs following the collapse of the Fundao dam in Brazil - Oliveira Coimbra, Keyla Thayrinne; Alcantara, Enner [UNESP]; Souza Filho, Carlos Roberto de (Elsevier B.V., 2021)
One of the worst socio-environmental disasters to mark the history of Brazil and the world occurred in November 2015 and involved the mining sector. The collapse of the Fundao dam released approximately 43 million m(3) of iron ore tailings, which moved downstream to reach the Doce River. This resulted in the contamination of water, soil, and sediments along the entire course of the river, which also affected its mouth in the Atlantic Ocean. Four years after the disaster, several socio-environmental problems continue to persist in the affected areas. In this context, the reservoirs built along the Doce River deserve special attention as they are artificial environments that are highly vulnerable to changes in water parameters. This study aims to determine water quality indicators of these reservoirs using remote sensing data and image processing methods, including semi-analytical algorithms, to comprehend the progress of eutrophication processes. Operational land imager/Landsat-8 data (from 2013 to 2019) were used to map the suspended particulate matter (SPM), euphotic zone (Z(eu)) and chlorophyll-a (Chl-a) before and after the collapse. The results showed significant changes in SPM and Z(eu) in the reservoirs after the collapse. Non-conformity of these parameters is observed even now, and they tend to intensify during rainy periods when resuspension processes of sediments occur. Moreover, there has been an increase in the eutrophication of reservoirs as noticed by the significant increase in Chl-a after the disaster, especially in January, July, and August. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Eutrophication; Fundao tailings dam collapse; Doce river reservoirs